Integrasi Metode Pengalamatan Dinamis Treecast Dan Sinkronisasi Waktu Dengan Reference Broadcast Synchronization Pada Sensor Network - Maulita Intan Kripsita; Sabriansyah Rizqika Akbar; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Technology is now growing rapidly. One of them is Wireless Sensor Network (WSN) which is a network connected to devices such as sink node, router and sensor node. However, the development is a problem if the node sensor in the Wireless Sensor Network to configure it manually. Each node in Wireless Sensor Network have the same frequency when communicating and local time is different, allowing node to send data at the same time that resulted in a collision data so that data is not received and can not be propagated on other nodes. To solve this problem, then applied the method Treecast and Reference Broadcast Synchronization (RBS) will be integrated. Treecast gives the address to the sensor node in a dynamic and keep the communication in order to remain able to do even if there are failures. While Reference Broadcast Synchronization is able to provide time equalization on each node. With a node beacon as the sender of the reference, beacon to give the order to synchronise. Next the nodes receiver synchronizes and share time with other receivers to get time difference and is used as time synchronization reference. This makes the node is able to provide guarantee in terms of sending and receiving data and no collision. The research results obtained are capable of dynamic addressing Treecast implemented in practice and is able to provide an address and a time to get the address of each sensor nodes in a sensor network network.Then for time synchronization using Reference Broadcast Synchronization node receiver uses 4 and 5 reference package that can achieve accuracy time synchronization to the unit millisecond time.